OTU-008 Growth in participation, registrations and data maturity in the UK IBD registry: focus on biologics. (8th June 2018) - Shawihdi, Mustafa; Razanskaite, Violeta; Cummings, Fraser; Bloom, Stuart; Bodger, Keith; Bodger, Keith
Abstract : Introduction: The UK IBD Registry (IBD-R) provides a standardised dataset and alternative methods for local teams to record structured electronic data in routine care. The infrastructure enables collection of data for local use and upload of anonymized data centrally (each quarter). Registry participation allows sites to demonstrate engagement with national audit (e.g. Biologics Audit, listed on the NHS Quality Accounts) and access to centrally-developed analytics and reporting. Methods: To evaluate growth in establishment of local biologics registers using the IBD-R, we analysed three uploads of data (March, June and Sept 2017) with a focus on key data items required for producing site-level reports for patients treated with these agents (from a basic to more granular-level detail, using the 'biologics events' dataset). We generated Quarterly Reports and distributed to centres, seeking feedback to inform future iterations. Results: Participating centres grew by 59% (32 to 51) and number of sites contributing biologics events more than doubled (16 to 37). Total registered patients in the IBD-R increased from 24 633 to 31 613. Biologics Events: For adults with CD, submitted initiation events increased >6 fold (472 to 3126 patients), post-induction review ~3 fold (709 to 2, 022) and 12 month review >19 fold (22 to 437). Agents used for adult CD [UC]: Remicade 1423 [450]; Humira 1675 [311]; Inflectra 345 [236]; Remsima 398 [225]; Vedolizumab 186 [201]; Ustekinumab 16 [0]. Data completeness varied by item, e.g. recording of 'naïve' status (y or n) was static at ~50%; categorization of clinical indication consistently high at >80% of cases. Outcome measures: By Sept 17, Physician Global Assessment (PGA) was reported at 1053 initiation events for CD (62%) and UC 940 (66%); and at 1537 (97%) and 1248 (80%) post-induction reviews showing rapid adoption, but data for disease activity indices (HBI or SCCAI) remained static at around 10%. The next upload (Feb 2018) contains almost 40 000 records from 63 sites and confirms continuing growth (analysis in progress). Conclusions: There has been significant increase in participation and in the breadth and depth of data being submitted to the UK IBD-R, particularly for biological therapies. Patterns of outcome data collection suggest clinical teams favour simple global outcome measures to formal activity indices – likely reflecting the added burden of administering and recording the data. However, the feasibility of site-level reporting to support local biologics registries is now established. Funded by: Crohn's and Colitis UK